Case Study: Maintenance Proposal of Press Parts Production for Minimize Waste by Lean Manufacturing – Value Stream Mapping (VSM) - Dessy Agustina Sari; Sukanta Sukanta (Universitas Lampung, 2017)
Abstract—Higher competition in businesslike field demanded each company acted as a value creator with progressive fixing performance. One of effort in increasing productivity was reducing waste. Enterprise T have seven type of extravagance were over production, transportation, inventory, over processing, motion waiting and defect. Minimize waste have bond with production time which could increase efficiency on using electricity and decreased lead time. Production process in this company showed non-value added time such as excessively material transportation in picking area and so the workers too much waited for the next schedule activity. This condition caused higher product lead time. Lean manufacturing idea necessary was implemented with using tool Value Stream Mapping – VSM. This strategy would resumed for the company maintenance and the result showed that lacking as much 26,45% of lead time could be a problem solution. Reducing lead time could be higher if the company have applied and played continue improvement.Keywords—lead time, lean manufacturing, value stream mapping.